PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKANKEPERCAYAAN DIRI DAN PRESTASI BELAJAR SISWA - Ella Andriani; Johanes Sapri (UNIB Press, 2022)
This study aims to describe the application of the Discovery Learning learning model to increase self-confidence and learning achievement in class VIII students at Mts Al Azhar Pagaralam. The formulation of the problem in this thesis is: How is the Application of the Discovery Learning Learning Model to increase students' confidence in Social Studies Subject VIII at Mts Al Azhar Pagaralam, Is the Application of the Discovery Learning Learning Model to improve student achievement in Social Studies Subject VIII at Mts Al Azhar Pagaralam and How is the effectiveness of the application of the Discovery Learning Learning Model to improve student achievement in Social Studies Subject VIII at Mts Al Azhar Pagaralam. thesis research It aims to describe the application of the Discovery Learning Learning Model to increase students' confidence in Social Studies Subject VIII at Mts Al Azhar Pagaralam, to describe the application of the Discovery Learning learning model to improve student achievement in Social Studies VIII Subject at Mts Al Azhar Pagaralam and to describe the effectiveness Application of the Discovery Learning Learning Model to improve student achievement in Social Studies Subject VIII at Mts Al Azhar Pagaralam. This thesis uses classroom action research with the use of research methods combined ( mixed method research) which is a combination of action research ( action research) and research experiments ( experimentre search ). Based on the results of the study, it was proven that the application of the discovery learning model could increase students' self-confidence from one cycle to the next. Therefore, the application of the discovery learning model needs to be done to increase students' self-confidence and the discovery learning model is able to improve student achievement, this is evident from the increase in the pre-test to post-test scores in each cycle. Therefore, it is necessary to apply the discovery learning model to improve student achievement. This study has proven that the application of the discovery learning model can effectively improve student achievement in social studies subjects. Therefore, the application of the discovery learning model is very effectively applied to improve student achievement at Mts Al Azhar Pagaralam.